PENGARUH KECENDERUNGAN BELAJAR ONLINE SELAMA COVID-19 TERHADAP MINAT BELAJAR ANAK DI KAMPUNG PASULUHAN KECAMATAN WALANTAKA KOTA SERANG - E. Nita Prianti; Susilawati (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to determine the effect of online learning tendencies during Covid-19 on children's learning interest in Pasuluhan Village, Walantaka District, Serang City. The background to this problem is the low interest in learning children online, causing low learning achievement for children, lack of parental assistance, online learning is considered less effective, internet access is inadequate. The formulation in this study is "How Big is the Effect of Online Learning Trends During Covid-19 on Children's Interest in Learning Pasuluhan Village, Walantaka District, Serang City". The method in this study uses quantitative methods using statistical data with several tests, namely validity tests, reliability tests, correlation tests, determination tests and hypothesis testing. The sample in this study were 60 respondents. The results obtained in this study are that there is a significant effect between variable X and variable Y, namely there is an influence of Online Learning Trends During Covid-19 on Children's Learning Interests, which is reaching an effect of 23.1%. Based on the results of the research calculations, it means that Ho is rejected and Ha is accepted